Intelligence and gender as predictors of academic achievement among undergraduate students. - Naderi, Habibollah; Abdullah, Rohani; Tengku Abdul Hamid, Tengku Aizan; Sharir, Jamaluddin (EuroJournals, Inc., 2008)
There has been significant discussion concerning the causal preference of intelligence, gender and academic achievement. A number of researchers' have examined intelligence, gender and academic achievement as equal constructs. Others consider that intelligence and gender as predictors of academic achievement are reciprocal. At a standstill, others emphasize that intelligence and gender predict to achievement. This study examined intelligence and gender as predictors of academic achievement among undergraduate students. Participants (N= 153, 105 = male & 48= female) completed intelligence test and the cumulative grade point average (CGPA). The finding showed a lower correlation independent variables (score of intelligence and gender)and CGPA in this study. A multiple regression analysis revealed an interesting pattern of relationship. Further, multiple regression analyses indicated that intelligence and gender explained 0.019 of the variance in academic achievement.